Factor Affecting Customer Satisfaction of Mobile Banking Services of Commercial Bank in Kathmandu Valley - Thakuri, Narendra; Dhakal, Ajaya; Danuwar, Ranjana Kumari; Baral, Deep Kumar; Koirala, Amita (Journal of Innovation in Academia, 2023)
Mobile banking has achieved a great importance in Nepal’s banking sector. Though majority of Nepalese banks have recognized the importance of understanding customer psychology and are highly conscious of it. some banks often struggle to keep pace with customer expectations. This paper specifically targets commercial bank customers and aims to uncover their differential perceptions. The study aims to identify the most influential factors that affect customer satisfaction and retention in mobile banking and determine their relative impact. The Exploratory research design was adopted as the main research paradigm to discover the reality. The data was evaluated quantitatively by using both descriptive and inferential statistics. Convenience sampling has used data collection and Structural Equation Modeling (SEM) was used to analyze the relationships from 403 responses. The research findings indicated that security, responsiveness, and convenience have a significant impact on customer satisfaction, while cost and relative advantage have a negligible impact. However, although customer satisfaction and loyalty are strongly related, these factors are not directly related to loyalty. This finding holds theoretical relevance for the Service Quality Theory. The scope and depth of this study is limited to banking customers of Kathmandu Valley. Further studies should include other variables to better understand the underlying relationship between customer satisfaction. Implication includes researchers, banking authority and policy makers who focus on enhancing mobile banking services. Mobile banking is an essential aspect that demands greater priority. Significant enhancements must be made to strengthen security measures, ensure stable service and support, and establish a fairly structured cost system to ensure better modern banking and financial systems.